Red ALyC, la hemeroteca en línea en ciencias sociales http://www.redalyc.com - Aguado, Eduardo; Chávez, Salvador; Sandoval, Eduardo Andrés; Rogel, Rosario (CIENCIA ergo-sum; Vol. 11 Núm. 1 (2004): CIENCIA ergo-sum (marzo-junio 2004), 2015)
_